Empirical insights into resilience-based strategies for addressing haze pollution: enhancing green infrastructure and urban resilience - Raza, Ali; Zhou, Jin; Imran, Muhammad; Sui, Hongguang (Frontiers in Environmental Science, 2025)
Amid growing concerns about haze pollution and its detrimental effects on ecological systems and public health, this study proposes a novel approach to addressing this pressing issue. Drawing on a cohort of 120 environmental academics, the research employs advanced second-generation statistical methodologies, including partial least squares structural equation modeling, to introduce an innovative strategy rooted in resilience theory. This approach emphasizes resilience as the foundation for advancing green infrastructure and urban sustainability in the context of haze pollution. The findings highlight resilience as a key driver in fostering green infrastructure and urban resilience through the integration of smart technology adoption, nature-based solutions, and environmental digital platforms. These factors collectively enable urban environments to effectively tackle the dual challenges of climate change and pollution. Recognizing haze pollution as a widespread concern, particularly in developing nations, the study provides actionable strategies with global relevance. By offering practical insights, this research contributes to the global pursuit of sustainable urban development and resilience.